L’objectivité en trompe-l’œil - Maria Holubowicz (Communication)
Le Figaro’s framing of the creation of France’s Ministry of Immigration, Integration, National Identity, and Mutually Supportive Development (MIIIN) in 2007, under president Nicolas Sarkozy, shows that this right-leaning newspaper uses different types of journalistic artifacts to objectify coverage of this event and give the impression of encouraging debate about it by applying a strategy based on the appearance of non-engagement of today's general press.